And then you die-- - Johansen, Iris. (Bantam Books, 1998)
When Bess Grady and her sister arrive in Mexico on vacation they are expecting paradise. Instead they find every person in the village is dead, killed in a bloodless carnage. The sisters are aided only by a mysterious agent who holds the key to stopping a vicious weapon aimed at America.